2022
DOI: 10.3390/cancers14246232
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Cancer Inflammation Prognostic Index as a Superior Predictor of Short- and Long-Term Outcomes in Patients with Stage I–III Colorectal Cancer after Curative Surgery

Abstract: Inflammatory reactions play a crucial role in cancer progression and may contribute to systemic inflammation. In routine clinical practice, some inflammatory biomarkers can be utilized as valuable predictors for colorectal cancer (CRC). This study aims to determine the usefulness of a novel cancer-inflammation prognostic index (CIPI) marker derived from calculating carcinoembryonic antigen (CEA) multiplied by the neutrophil-to-lymphocyte ratio (NLR) values established for non-metastatic CRCs. Between January 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Based on neutrophil, lymphocyte, and CEA levels, Su et al 19 developed the CIPI in 2021 to predict survival in patients with metastatic CRC treated with regorafenib. A subsequent study by You et al 22 also showed that the CIPI is a reliable and easy-to-use clinical factor for predicting CRC outcomes. However, few studies are available on the prognostic value of the CIPI in patients with CRC.…”
Section: Discussionmentioning
confidence: 95%
“…Based on neutrophil, lymphocyte, and CEA levels, Su et al 19 developed the CIPI in 2021 to predict survival in patients with metastatic CRC treated with regorafenib. A subsequent study by You et al 22 also showed that the CIPI is a reliable and easy-to-use clinical factor for predicting CRC outcomes. However, few studies are available on the prognostic value of the CIPI in patients with CRC.…”
Section: Discussionmentioning
confidence: 95%
“…PNI was calculated by combining serum albumin levels with the total peripheral lymphocyte count in peripheral blood [ 17 ]. NLR was defined as the ratio of neutrophil-to-lymphocyte count, and CIPI was calculated as CEA (ng/ml) × NLR [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…PNI was calculated by combining serum albumin levels with the total peripheral lymphocyte count in peripheral blood [17]. NLR was de ned as the ratio of neutrophil-to-lymphocyte count, and CIPI was calculated as CEA (ng/ml) × NLR [18,19].…”
Section: Patientsmentioning
confidence: 99%